“ENGLISH TENSE PRACTICE” APPLICATION FOR FOSTERING THE STUDENTS’ FAST AND CRITICAL THINKING ON ENGLISH GRAMMAR - Mabaroh, Barotun; Setyowati, Lestari (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The adjustment to the digital era must be accommodated for quality education. Due to this statement, English Language Teaching (ELT) in higher education should be able to lead the implementation of optimizing learning with technological support. Thus, grammar lecturers are to recognize “English Tenses Practice” application to foster the students’ fast and critical thinking. The present research was qualitative description (QD). The researchers knew the lecturer had taught the students using constructive approach throughout the ice breaking Grammar on my fingers , playing “English Tenses Practice” application, and discussion. In the discussion, the lecturers fostered the students’ critical thinking by asking the objective reasons for their answers. The researchers could also describe the application provides a flash review of the twelve English tenses (not sixteen), examples, practices, and multiple choice and arranging sentence tests. The application demanded the students to fast thinking through both tests since the application provides them with a limited duration. With many facts regarding the implementation, the researchers could highlight the advantages and disadvantages of using the application. The researchers also verified that technology needs to develop more for giving chances to elaborate the students’ reasoning skill rather than instant answering which eventually allow cheating among them. Last, lecturers and further researchers should read this research results to take the best future actions both for their teaching and analytical studies